Quantifying the relationship between irrigation activities and wetlands in a northern Colorado watershed: assessing this added value of irrigation - Smith, Meagan Blake, author; Arabi, Mazdak, advisor; Fontane, Darrell, committee member; Goemans, Christopher, committee member (Colorado State University. Libraries, 2012)
The construction over the past 130 years of an extensive canal system throughout Colorado has allowed for the spread of irrigated agriculture further and further from the water source. Irrigation activities and associated return flows serve multiple benefits to the surrounding ecosystem health and function, specifically the creation and maintenance of wetlands that would otherwise not exist. This research aims to quantify the relationship between cropland irrigation and down gradient "incidental" wetlands, to allow for the valuation of ecosystem services provided by water in agriculture. Non-linear and multiple-linear regression analyses were used in combination to explain the variability in the size of "incidental" wetlands in a northern Colorado watershed, in response to irrigation application and infrastructure within the contributing areas of each wetland. The explanatory variables included amount of area under flood and sprinkler irrigation, irrigation conveyance structures, and controls for heterogeneities in the landscape, including runoff potential and shallow groundwater flow potential. The analyses were performed using aggregated landscape properties at various distances from the edge of the wetlands, from 50 m to 500 m, in an attempt to identify a spatial area of influence for irrigation activities in the study area. Further analyses included evaluating the impact of changing irrigation scenarios on the size of "incidental" wetlands. The simulated scenarios included increasing application efficiency by converting all flood irrigated lands to sprinkler irrigation; and increasing conveyance efficiency by lining all existing canals. Research findings include (i) the most significant explanatory variables, irrespective of distance from wetland, were amount of flood-irrigated lands and length of irrigation conveyance structures, (ii) irrigation activities within 200 m of a wetland explained the greatest variability in wetland size (R2adj = 0.50), (iii) increasing runoff potential in the contributing areas, represented by area-weighted curve number values, increased the impact of irrigation variables on the size of "incidental" wetlands, and (iv) increasing irrigation efficiencies in the study area consistently resulted in decreasing total wetland area. Furthermore, an ecosystem benefits transfer model was utilized to estimate the dollar value of the ecosystem services provided by the "incidental" wetlands in the study area. At an estimated value of $5,647/ha, the ability to evaluate the impact of changing irrigation practices on nearby wetlands may influence the decision process of both landowners and water planners.
Keywords: wetlands; irrigation canal; irrigation; GIS; ecosystem services